The effects of incentive schemes, working relationships and risk attitudes on the propensity to report a questionable act - Abdul Kareem, Salma Parveen (2013)
This paper examines whether incentive schemes, working relationships and risk attitudes affect the propensity to report a questionable act in a hypothetical situation. Results from our experiment, which involved 258 accounting students, provide no evidence to support our hypothesis that when a close relationship exists between the wrongdoer and decision-maker, a penalty scheme increases the propensity of whistle-blowing more than a reward scheme. Instead we found that reward scheme, but not penalty scheme, increases whistle-blowing when there is a close relationship. We also found no evidence to suggest that penalty scheme increases the whistle-blowing propensity of financially risk averse people more than that of financially risk taking people.